Investigation of the performance of Some Grape Cultivars Grown in Mecitözü (Çorum) Ecological Condition - Rüstem Cangi; Ergün Demir (Turkish Journal of Agriculture: Food Science and Technology)
In this study, optimum harvest times, cluster and berry characteristics of four grape cultivars (Hasandede, Öküzgözü, Boğazkere, and HorozKarası) grown in Mecitözü (Çorum) ecological conditions were determined. In two consecutive years (2017-2018) yield, clusters, berry properties, water-soluble solid content, pH, titratable acidity, maturity index properties were determined. Some biochemical changes in grape varieties were followed during the ripening periods in the second year. The highest yield in both years was obtained from the variety of Horoz Karası (1421.2 and 1504.8 kg/da), while the lowest yield was obtained from Öküzgözü (619.4 and 578.31 kg/da). During the harvest period, the total acidity and pH values must be changed according to years and varieties. The total soluble solids (TSS) and pH values increased with maturation, whereas the total acidity was found to decrease till the last observation date. During the harvest period, all varieties reached optimum harvest maturity in both years.